Re-defining the requirements engineering process improvement model - Solemon B.; Sahibuddin S.; Ghani A.A.A. (2023)
A specialized Requirements Capability Maturity Model (R-CMM) was created by a group of researchers from UK as an attempt to support the requirements engineering phase of software development. The validation performed to this model shows that it has some potentials to be a useful tool for both practitioners and researchers in the field of process improvement and requirements engineering. However, the RCMM focuses on the requirements engineering process defined within the retired Software Engineering Institute's (SEI's) Software Capability Maturity Model (SW-CMM) process improvement framework. To continue its relevance and usefulness, we re-define the whole R-CMM within the characteristics of the latest Capability Maturity Model for Integration (CMMI) for Development (CMMI-DEV) v1.2. This paper describes how the CMMI-DEV characteristics are used to re-define the R-CMM, and rationale for re-building the requirements engineering model based on the latest process improvement framework. Also, this paper explains how the redefined R-CMM adapts to the goals and practices set by the CMMI-DEV. 2009 IEEE.